Renal myopericytoma: A case report with a literature review - Yunhan Huang; Qian Yang; Haidi Lv; Baihong Guo (Urology Case Reports, 2024)
Myopericytoma is a rare soft tissue tumor characterized by differentiation into perivascular muscle-like cells or perimuscular cells. This tumor primarily affects adults and is uncommon in children. It is predominantly found in the subcutaneous soft tissues of the distal limbs, and cases originating in the kidney are exceedingly rare. In this report, we present a case of a patient with renal myopericytoma admitted to our hospital. We also summarize the diagnostic and therapeutic features by reviewing relevant domestic and international literature.